Implementation of the Lupus Low Disease Activity State in Pediatric Rheumatology Care: The Role of the Visual Analog Scale - Ekemini A. Ogbu; Anna Carmela P. Sagcal‐Gironella; B. Anne Eberhard; Jennifer M. Huggins; Marisa S. Klein‐Gitelman; Karen Onel; Chen Chen; Bin Huang; Hermine I. Brunner (ACR Open Rheumatology)
Objective We compared the measurement properties of a traditional physician global assessment of disease activity (PhGA) 10‐cm visual analog scale (PhGA0–10) with that of the three‐point numeric scale (PhGA0–3) in childhood‐onset systemic lupus erythematosus (cSLE) as part of the childhood Lupus Low Disease Activity State (cLLDAS). Methods We used a secondary data analysis from a convenience sample of 100 patients with cSLE followed every three months for up to seven visits. Ratings of PhGA0–10, PhGA0–3, parent assessment of patient well‐being (ParGA) (range: 0= very poorly, 10 = very well), disease activity as measured by the SLE disease activity index 2000 (SLEDAI‐2k), Safety of Estrogens in Lupus Erythematosus National Assessment (SELENA) SLEDAI, and the British Isles International Lupus Activity Group index (BILAG; A = 9, B = 3, C = 1, D/E = 0) were compared. After linear transformation of PhGA0–10 to a 0 to 3 range (tPhGA0–10), the frequency of PhGA0–3 ≤1 was assessed to estimate the impact of scale type on the scoring of the cLLDAS. Results In 600 visits, the median (range) scores of PhGA0–10, PhGA0–3, SLEDAI‐2k, SELENA‐SLEDAI, and BILAG were 2 (0–10), 1(0–3), 4 (0–28), 4 (0–32), and 2 (0–28), respectively. PhGA0–10 and PhGA0–3 ratings were strong to moderately correlated with (r = 0.73; P < 0.0001) and with more variability for PhGA0–3 ≥2. SELENA‐SLEDAI and SLEDAI‐2k scores were moderately correlated with PhGA0–10 (r = 0.56/0.54; P < 0.0001). ParGA values were weakly correlated with all other measures considered (all r = −0.19 to −0.34). There were 490 of 600 visits with PhGA0−3 ≤1 and 497 of 600 visits with tPhGA0−10 ≤1 (κ (SE) =0.59 (0.04), McNemar P = 0.4). Conclusion PhGA0–3 and PhGA0–10 have comparable measurement properties and yield almost identical cLLDAS rates when used in cSLE.